The Influence of Credit Approval Policy Through the 5C Principle (Character, Capacity, Capital, Collateral, Condition of Economy) on Credit Asset Quality and Its Implications on NPL (Non-Performing Loan) Level PT. BPR YSL Bandung - Teti Ofianti; Tatang S Herisman; Cecep Taofiqurrochman (Eduvest - Journal of Universal Studies, 2026)
This study aims to analyze the effect of credit approval policies based on the 5C principles on credit asset quality and their implications for the level of Non-Performing Loans (NPL) at PT. BPR YSL Bandung. The phenomenon of fluctuating NPL levels that exceed the maximum threshold set by the Financial Services Authority (OJK) highlights the importance of evaluating the effectiveness of credit approval policies. This research adopts a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to internal bank employees involved in the credit approval and monitoring process, while secondary data were obtained from NPL reports covering the period from June 2024 to May 2025. Path analysis was employed to examine both direct and indirect relationships among variables. The results indicate that credit approval policies implemented through the 5C principles have a positive and significant effect on credit asset quality. Furthermore, credit asset quality has a significant influence in reducing the level of NPL. The findings also reveal that credit approval policies have a direct and significant effect on NPL. In addition, credit asset quality acts as a mediating variable that strengthens the relationship between credit approval policies based on the 5C principles and NPL levels. These results emphasize that consistent and comprehensive implementation of the 5C principles is essential to maintain credit asset quality and improve the financial health and stability of rural banks. This study is expected to provide valuable insights for bank management in enhancing credit risk management strategies.